The Poetics of Poetic Necessities - aabad, Ahmed; Sebbâh , Belmersli (El Omda in Linguistics and Discourse Analysis, 2023)
Poetry is distinguished from other literary genres, by its emotional language based on respect for feelings and feelings, and the sympathetic custom through which its verses and poems are woven, without taking into account the positive language that has its rules and the linguistic community wraps around it, evading this by the topic of poetic necessities, which met a great wave of The many and different opinions of grammarians and linguists, despite the position, merit and status of poetry over other sciences in the Arab environment, especially grammar and rhetoric, as poetry in them represented the witness to their rules and sciences, and one of the most prominent issues in which this was seen; Presentation and delay, dhikr and omission, substitution and others. Therefore, poetic necessities were a single field of study within the parameters of poetic language.